2014
DOI: 10.3109/10717544.2014.965801
|View full text |Cite
|
Sign up to set email alerts
|

Development and clinical study of submicronic-atropine sulphate respiratory fluid as a novel organophosphorous poisoning antidote

Abstract: Context: Increased use of organophosphate insecticides (OPI) and possibility of terror groups using stocks of nerve agents underscore the need to develop effective and safe antidotes. While intramuscular administration of antidotes like atropine sulphate (AS) has certain lacunae, intravenous route may not be always feasible in emergency field conditions. Objective: Objective was (a) to develop a novel inhalable submicronic-AS respiratory fluid as potential antidote for OPI poisoning, (b) in-vitro and in-vivo e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Earlier studies reported, according to an ADME (absorption, distribution, metabolism, and excretion) and toxicity study, atropine crosses the blood-brain barrier, which is crucial for efficient treatment of viral illness [ 32 ]. Moreover, submicronic atropine sulfate respiratory fluid has the potential to be employed as a prophylactic strategy against organophosphorous poisoning, with various advantages over intramuscular injection, including early blood absorption and atropinization [ 33 ]. Calcium-dependent protein kinases play important roles in calcium signaling in T .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies reported, according to an ADME (absorption, distribution, metabolism, and excretion) and toxicity study, atropine crosses the blood-brain barrier, which is crucial for efficient treatment of viral illness [ 32 ]. Moreover, submicronic atropine sulfate respiratory fluid has the potential to be employed as a prophylactic strategy against organophosphorous poisoning, with various advantages over intramuscular injection, including early blood absorption and atropinization [ 33 ]. Calcium-dependent protein kinases play important roles in calcium signaling in T .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, submicronic atropine sulfate respiratory fluid has the potential to be employed as a prophylactic strategy against organophosphorous poisoning, with various advantages over intramuscular injection, including early blood absorption and atropinization [33]. Calciumdependent protein kinases play important roles in calcium signaling in T. gondii and C. parvum, making them interesting targets for antiparasitic drug research [34,35].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%